Fundamental of Entrepreneurship ENT300 : Meella Laundry / Monica Elizabeth Michael ... [et al.] - Michael, Monica Elizabeth; Abdul Hamid, Nurecca Miliyani; Mohamad Toni, Nur Lyanna; Se-Aie, Noor Asmiza; Wan Za’aba, Sharifah Ruhiza; Let, Zulaikha (2015)
Meella Laundry is a partnership business in the form of enterprise which consists of six members. We chose laundry business because it doesn’t need any raw materials and our sources, for example, detergent does not expire quickly. Plus, this partnership is perfect for use, as we all share the same compassion, which is to give the best services to our customers.